Cultural Governance: A Feasible Path for Promoting Rural Revitalization under the Background of the Integration of Culture, Sports and Tourism - Tu, Duoyang (International Journal of Social Sciences and Public Administration, 2025)
Rural revitalization is an important deployment by the Party and the state to promote high-quality economic development in rural areas, and it is the key to driving the transformation of rural civilization and realizing the great rejuvenation of the Chinese nation. Rural cultural governance is an important form of governance for achieving the transformation of rural areas from traditional civilization to modern civilization. In the process of promoting Chinese-style modernization, to achieve modernization in rural areas, it is necessary to closely integrate rural culture with the development of The Times, and improve the quality of cultural life of farmers while maintaining the characteristics of rural culture. The breakout of the "Two Rivers and Two Villages" sports events has provided a new model for rural cultural governance and achieving rural economic development in promoting rural revitalization. It is found from the cases that cultural governance in rural areas can be effectively promoted by strengthening multi-party co-governance, innovating governance forms, expanding the public space of rural culture and enriching the supply of high-quality cultural products.